Fatores de risco para celulite em adolescentes - Soares, Juliana Laudiceia Marques [UNIFESP] (2019)
Introduction. The cellulite is characterized as an irregular appearance of skin surface, with a "padded" or "orange peel" aspect on the thighs and gluteal regions and, less frequently, on the arms and abdomen, predominantly in women after puberty. Although the etiopathogenesis is still not fully understood, cellulite is considered a multifactorial disorder, involving primary, anatomic or structural alterations of the adipose tissue and alterations of the dermal connective tissue. The most relevant factors include: fat herniation towards the dermal connective tissue, facilitated by the presence of fine and perpendicular hypodermic fibrous septa; the biochemical and metabolic differences in relation to normal fat and the architectural changes related to sex in different regions of the body. Objective: To evaluate the risk factors for the appearance of cellulite and its impact on quality of life. Methods: This is a cross-sectional observational study. A total of 184 adolescents aged 12 to 18 years, mean of 15 years were included. Genetic familial, gynecological hormonal factors, physical activity, nutrition, body composition and anthropometry were evaluated as well as cellulite severity and its impact on quality of life. Results: The variables that showed significant as a risk factor for cellulite were: BMI (p˂0.001), time since menarche (p = 0.037), carbohydrate by energy (p = 0.006), water consumption per day (p = 0.037), family history (p = 0.003) and weekly physical activity (p˂0.001). Conclusion: Genetic familial, gynecological hormonal, nutritional, anthropometric factors and physical activity showed direct relation to development and severity of cellulite, which reinforces its multifactorial character. The disclosure of this study will be important to point out possible physiopathological mechanisms and to alert the adolescents about the risk factors associated with the onset and worsening of this condition.